Self-cleaning rubber connecting pipe for drainage system

By using copper-mercaptobenzimidazole/boron nitride-loaded copper nanoclusters in rubber connecting tubes, the problem of rubber connecting tubes breeding bacteria and moss in humid environments is solved, and its antibacterial and lubricating properties are improved, and the antibacterial and lubricating properties are maintained. Clean status of the inner wall of the tube.

CN119264572APending Publication Date: 2025-01-07ANHUI YONGZHENG SEAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411602757.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The rubber connecting pipes in the existing drainage system are prone to breed bacteria and moss in humid environments, resulting in odor pollution and affecting the living environment.

Method used

Using raw materials such as ethylene propylene ternary rubber, carbon black, calcium carbonate, paraffin oil, polytetrafluoroethylene, zinc oxide and copper-mercaptobenzimidazole/boron nitride, it is stabilized by hydrothermal synthesis. The copper nanoclusters improve the antibacterial and lubricating properties of rubber connecting tubes.

Benefits of technology

It significantly reduces the adhesion rate of dirt, keeps the inner wall surface of the rubber connecting pipe clean, improves antibacterial and lubricating properties, extends the service life of nano-copper, and prevents corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005128732350000051
    Figure BDA0005128732350000051
  • Figure BDA0005128732350000071
    Figure BDA0005128732350000071
  • Figure BDA0005128732350000081
    Figure BDA0005128732350000081
Patent Text Reader

Abstract

The invention discloses a self-cleaning rubber connecting pipe for a drainage system, and belongs to the technical field of drainage pipes, the rubber connecting pipe comprises the following raw materials: 30-35 parts of ethylene propylene diene monomer, 2.5-2.8 parts of carbon black, 1-1.2 parts of an accelerant, 15-20 parts of calcium carbonate, 3.0 parts of paraffin oil, 2.0-2.5 parts of polytetrafluoroethylene, 1.5 parts of zinc oxide and 1.2-2.2 parts of copper-mercaptobenzimidazole / boron nitride, through a hydrothermal synthesis method, boron nitride with a two-dimensional layered structure is taken as a carrier, copper-mercapto benzimidazole is loaded on the carrier to form a copper-mercapto benzimidazole / boron nitride material, the copper-mercapto benzimidazole / boron nitride material is added into a rubber connecting raw material, the adding amount is controlled, and the lubricating property and the antibacterial property of the rubber connecting pipe are improved through the synergistic effect of the three components, so that the surface of the rubber connecting pipe is kept clean.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of drainage pipes, and in particular relates to a self-cleaning rubber connecting pipe for a drainage system. Background Art

[0002] Household bathtubs or wash basins are fixed, and their bottom is connected to the sewer with a conduit. If the connection interface is not sealed tightly, it will cause leakage. The elastic deformation effect of rubber tubes is very good. During the installation of pipelines, the connection between pipes often has the problem of non-concentricity. The rubber connecting pipe has a certain deflection angle, which greatly facilitates the connection of the pipeline, and the interface has better sealing.

[0003] At present, most connecting pipes are S-shaped or U-shaped pipes, and their main function is to isolate the odor of the sewer pipe or other living things from seeping back along the pipe or crawling into the home. Although the commonly used S-shaped or U-shaped pipes have a certain barrier effect, there will be a certain amount of liquid at the S-shaped or U-shaped bend to serve as a barrier. Affected by this design, if some dirt adheres to the inner wall of the connecting pipe during the drainage process, it will cause the presence of dirt in the liquid that can provide nutrition for bacteria. Moss and other bacteria will grow in a humid environment, and the odor will continue to be emitted into the home for a long time, affecting the living environment. Summary of the invention

[0004] Based on the above problems, the purpose of the present invention is to provide a self-cleaning rubber connecting pipe for a drainage system to solve the problem of bacterial growth and enable the rubber connecting pipe to have a self-cleaning effect.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] The present invention provides a self-cleaning rubber connecting pipe for a drainage system, which comprises the following raw materials in parts by weight:

[0007] 30-35 parts of EPDM rubber, 2.5-2.8 parts of carbon black, 1-1.2 parts of accelerator, 15-20 parts of calcium carbonate, 3.0 parts of paraffin oil, 2.0-2.5 parts of polytetrafluoroethylene, 1.5 parts of zinc oxide and 1.2-2.2 parts of copper-mercaptobenzimidazole / boron nitride.

[0008] Polytetrafluoroethylene has the characteristics of self-lubrication, non-combustion, high temperature resistance, and atmospheric aging resistance. EPDM and PTFE have good compatibility and are easy to mix evenly, which can improve the lubrication and mechanical properties of the material.

[0009] Furthermore, the accelerator is at least one of zinc diethyldithiocarbamate, zinc dibutyldithiocarbamate and zinc dimethyldithiocarbamate.

[0010] Further, the copper-mercaptobenzimidazole / boron nitride is prepared as follows:

[0011] Copper sulfate pentahydrate and 2-mercaptobenzimidazole are dissolved in deionized water, and then boron nitride nanosheets are added and mixed evenly to obtain solution A. NaBH4 and NaOH are dissolved in deionized water to form solution B. Solution A and solution B are mixed and stirred at room temperature for 1 hour. After complete precipitation, they are filtered and washed, and then dried to obtain copper-mercaptobenzimidazole / boron nitride.

[0012] 2-Mercaptobenzimidazole is often used as a rubber antioxidant. Its mercapto group gives it good antioxidant properties and metal complexing ability.

[0013] Furthermore, the molar ratio of copper sulfate pentahydrate to 2-mercaptobenzimidazole in the solution A is 1:1.

[0014] Furthermore, the concentration of copper sulfate pentahydrate in the A solution is 0.005 mol / L.

[0015] Furthermore, the mass ratio of boron nitride to copper sulfate pentahydrate in the solution A is 1:0.5-2.

[0016] Furthermore, the concentration of NaBH4 in the B solution is 0.02 mol / L.

[0017] Furthermore, the NaOH concentration in the B solution is 0.08 mol / L.

[0018] Furthermore, the volume ratio of solution A to solution B is 9:1.

[0019] Furthermore, the rubber connecting tube is prepared as follows:

[0020] Put EPDM rubber into an internal mixer, add polytetrafluoroethylene at 150°C and mix for 10 minutes, then add copper-mercaptobenzimidazole / boron nitride, mix for 5 minutes, add carbon black, calcium carbonate, paraffin oil and zinc oxide in sequence, continue mixing for 30 minutes, extrude and place for 10 hours to obtain a mixture, add an accelerator to the mixture, perform vulcanization and molding treatment, and obtain a rubber connecting pipe.

[0021] Beneficial effects of the present invention:

[0022] (1) The hydrothermal synthesis method of the present invention loads 2-mercaptobenzimidazole-stabilized copper nanoclusters on boron nitride. Nano-copper has excellent antibacterial properties. Since nano-copper is easily corroded, its performance will rapidly decline during long-term use. Adding 2-mercaptobenzimidazole as a protective agent can inhibit copper corrosion. In addition, the antibacterial performance of nano-copper has limitations. The introduction of imidazole groups can improve the antibacterial performance.

[0023] (2) The present invention uses boron nitride with a two-dimensional layered structure as a carrier, on which copper-mercaptobenzimidazole is loaded, thereby improving the dispersibility of copper nanoparticles and utilizing the double bond effect of 2-mercaptobenzimidazole and EPDM rubber to promote the compatibility of copper-mercaptobenzimidazole / boron nitride in EPDM rubber. The uniform doping of boron nitride improves the lubrication performance of the rubber connecting pipe, thereby reducing the dirt adhesion rate of the connecting pipe and keeping the inner wall surface of the rubber connecting pipe clean. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] Preparation of copper-mercaptobenzimidazole / boron nitride:

[0027] Copper sulfate pentahydrate and 2-mercaptobenzimidazole were dissolved in deionized water, and then boron nitride nanosheets were added and mixed to obtain solution A. The concentrations of copper sulfate pentahydrate and 2-mercaptobenzimidazole in solution A were both 0.005 mol / L, and the mass ratio of boron nitride to copper sulfate pentahydrate was 1:0.5. NaBH4 and NaOH were dissolved in deionized water to form solution B. The concentration of NaBH4 in solution B was 0.02 mol / L, and the concentration of NaOH was 0.08 mol / L. Solution A and solution B were mixed and stirred at a volume ratio of 9:1 at room temperature for 1 hour. After complete precipitation, they were filtered and washed, and dried to obtain copper-mercaptobenzimidazole / boron nitride.

[0028] Example 2

[0029] Compared with Example 1, the mass ratio of boron nitride to copper sulfate pentahydrate is adjusted to 1:1, and the other steps are the same as Example 1.

[0030] Example 3

[0031] Compared with Example 1, the mass ratio of boron nitride to copper sulfate pentahydrate is adjusted to 1:2, and the other steps are the same as Example 1.

[0032] Example 4

[0033] The rubber connecting pipe provided in this embodiment includes the following raw materials by weight:

[0034] 30 parts of EPDM rubber, 2.5 parts of carbon black, 1 part of zinc diethyl dithiocarbamate, 20 parts of calcium carbonate, 3.0 parts of paraffin oil, 2.0 parts of polytetrafluoroethylene, 1.5 parts of zinc oxide and 1.2 parts of copper-mercaptobenzimidazole / boron nitride prepared in Example 1

[0035] Prepare the rubber connecting pipe according to the above raw material ratio:

[0036] Put EPDM rubber into an internal mixer, add polytetrafluoroethylene at 150°C and mix for 10 minutes, then add copper-mercaptobenzimidazole / boron nitride, mix for 5 minutes, add carbon black, calcium carbonate, paraffin oil and zinc oxide in sequence, continue mixing for 30 minutes, extrude and place for 10 hours to obtain a mixture, add an accelerator to the mixture, perform vulcanization and molding treatment, and obtain a rubber connecting pipe.

[0037] Example 5

[0038] Compared with Example 4, the mass fraction of copper-mercaptobenzimidazole / boron nitride prepared in Example 1 in the raw material is increased to 1.8 parts, and the other steps are the same as Example 4.

[0039] Example 6

[0040] Compared with Example 4, the mass fraction of copper-mercaptobenzimidazole / boron nitride prepared in Example 1 in the raw material is increased to 2.2 parts, and the other steps are the same as Example 4.

[0041] Example 7

[0042] Compared with Example 5, the copper-mercaptobenzimidazole / boron nitride prepared in Example 1 in the raw materials is replaced by the copper-mercaptobenzimidazole / boron nitride prepared in Example 2, and the other steps are the same as in Example 5.

[0043] Example 8

[0044] Compared with Example 5, the copper-mercaptobenzimidazole / boron nitride prepared in Example 1 in the raw materials is replaced by the copper-mercaptobenzimidazole / boron nitride prepared in Example 3, and the other steps are the same as in Example 5.

[0045] Example 9-Example 10

[0046] Compared with Example 7, the ratio of raw materials is adjusted. The detailed ratio is shown in Table 1. The other steps are the same as Example 7.

[0047] Table 1

[0048]

[0049] Comparative Example 1

[0050] The difference from Example 4 is that copper-mercaptobenzimidazole / boron nitride is not added to the raw material of the rubber connecting pipe, and the other steps are the same as Example 4.

[0051] Comparative Example 2

[0052] The rubber connecting pipe provided in this embodiment includes the following raw materials by weight:

[0053] 30 parts of EPDM rubber, 2.5 parts of carbon black, 1 part of zinc diethyldithiocarbamate, 20 parts of calcium carbonate, 3.0 parts of paraffin oil, 2.0 parts of polytetrafluoroethylene, 1.5 parts of zinc oxide, 0.1 parts of copper nanoparticles, 0.25 parts of 2-mercaptobenzimidazole and 0.85 parts of boron nitride.

[0054] Prepare the rubber connecting pipe according to the above raw material ratio:

[0055] Put EPDM rubber into an internal mixer, add polytetrafluoroethylene at 150°C and mix for 10 minutes, then add copper nanoparticles, 2-mercaptobenzimidazole and boron nitride, mix for 5 minutes, add carbon black, calcium carbonate, paraffin oil and zinc oxide in sequence, continue mixing for 30 minutes, then extrude and place for 10 hours to obtain a mixture, add an accelerator to the mixture, perform vulcanization and molding treatment, and obtain a rubber connecting pipe.

[0056] Comparative Example 3

[0057] Preparation of copper / boron nitride:

[0058] Dissolve copper sulfate pentahydrate in deionized water, add boron nitride nanosheets, and mix well to obtain solution A. The concentration of copper sulfate pentahydrate in solution A is 0.005 mol / L, and the mass ratio of boron nitride to copper sulfate pentahydrate is 1:0.5. Dissolve NaBH4 and NaOH in deionized water to form solution B. The concentration of NaBH4 in solution B is 0.02 mol / L, and the concentration of NaOH is 0.08 mol / L. Mix solution A and solution B at a volume ratio of 9:1 at room temperature and stir for 1 hour. After complete precipitation, filter and wash, and dry to obtain copper / boron nitride.

[0059] The rubber connecting pipe provided in this comparative example includes the following raw materials by weight:

[0060] 30 parts of EPDM rubber, 2.5 parts of carbon black, 1 part of zinc diethyl dithiocarbamate, 20 parts of calcium carbonate, 3.0 parts of paraffin oil, 2.0 parts of polytetrafluoroethylene, 1.5 parts of zinc oxide and 1.2 parts of copper / boron nitride prepared in this comparative example

[0061] Prepare the rubber connecting pipe according to the above raw material ratio:

[0062] Put EPDM rubber into an internal mixer, add polytetrafluoroethylene at 150°C and mix for 10 minutes, then add copper / boron nitride, mix for 5 minutes, add carbon black, calcium carbonate, paraffin oil and zinc oxide in sequence, continue mixing for 30 minutes, extrude and place for 10 hours to obtain a mixture, add an accelerator to the mixture, perform vulcanization and molding treatment, and obtain a rubber connecting pipe.

[0063] Comparative Example 4

[0064] Preparation of 2-mercaptobenzimidazole-stabilized copper nanoclusters:

[0065] Copper sulfate pentahydrate and 2-mercaptobenzimidazole were dissolved in deionized water and mixed evenly to obtain solution A, wherein the concentrations of copper sulfate pentahydrate and 2-mercaptobenzimidazole in solution A were both 0.005 mol / L. NaBH4 and NaOH were dissolved in deionized water to form solution B, wherein the concentration of NaBH4 in solution B was 0.02 mol / L and the concentration of NaOH was 0.08 mol / L. Solution A and solution B were mixed and stirred at a volume ratio of 9:1 at room temperature for 1 hour, and after complete precipitation, the mixture was filtered and washed, and then dried to obtain 2-mercaptobenzimidazole-stabilized copper nanoclusters.

[0066] The rubber connecting pipe provided in this comparative example includes the following raw materials by weight:

[0067] 30 parts of EPDM rubber, 2.5 parts of carbon black, 1 part of zinc diethyldithiocarbamate, 20 parts of calcium carbonate, 3.0 parts of paraffin oil, 2.0 parts of polytetrafluoroethylene, 1.5 parts of zinc oxide and 0.35 parts of copper nanoclusters stabilized by 2-mercaptobenzimidazole

[0068] Prepare the rubber connecting pipe according to the above raw material ratio:

[0069] Put EPDM rubber into an internal mixer, add polytetrafluoroethylene at 150°C and mix for 10 minutes, then add copper nanoclusters stabilized by 2-mercaptobenzimidazole, mix for 5 minutes, add carbon black, calcium carbonate, paraffin oil and zinc oxide in sequence, continue mixing for 30 minutes, then extrude and place for 10 hours to obtain a mixture, add an accelerator to the mixture, perform vulcanization and molding treatment, and obtain a rubber connecting pipe.

[0070] The performance tests were performed on the rubber connecting pipes prepared in Examples 4 to 10 and Comparative Examples 1 to 4. The results are shown in Table 2.

[0071] Wear resistance: Use a wear tester to test the unit wear amount.

[0072] Antibacterial performance: Escherichia coli was used as the bacteria, and the test was carried out with reference to GB T 31402-2015 Test method for antibacterial properties of plastic surfaces.

[0073] Anti-aging performance: Refer to "GB_T 3512-2014 Hot air accelerated aging and heat resistance test for vulcanized rubber or thermoplastic rubber" and use method B for testing.

[0074] Table 2

[0075]

[0076]

[0077] As can be seen from Table 1, by gradually increasing the proportion of copper-mercaptobenzimidazole / boron nitride in the raw materials, the wear amount of the products of Examples 4-6 gradually decreases, the lubrication performance is improved, and the antibacterial performance is also improved. Adjusting the mass ratio of boron nitride and copper sulfate pentahydrate in the preparation of copper-mercaptobenzimidazole / boron nitride and increasing the proportion of copper and 2-mercaptobenzimidazole can enhance the anti-aging and antibacterial properties of the rubber connecting tube, but when the proportion is too high, some copper nanoparticles will agglomerate and accumulate on the surface of boron nitride, and its antibacterial performance will decrease. Compared with Example 1, the various properties of Comparative Example 1 are poor, and the effects of directly adding each component in Comparative Example 2 cannot be fully exerted, and the synergistic effect is reduced.

[0078] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0079] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A self-cleaning rubber connecting pipe for a drainage system, characterized in that: The following raw materials are included by mass: 30-35 parts of EPDM rubber, 2.5-2.8 parts of carbon black, 1-1.2 parts of accelerator, 15-20 parts of calcium carbonate, 3.0 parts of paraffin oil, 2.0-2.5 parts of polytetrafluoroethylene, 1.5 parts of zinc oxide and 1.2-2.2 parts of copper-mercaptobenzimidazole / boron nitride.

2. The self-cleaning rubber connecting pipe for drainage system according to claim 1, characterized in that: The accelerator is at least one of zinc diethyldithiocarbamate, zinc dibutyldithiocarbamate and zinc dimethyldithiocarbamate.

3. The self-cleaning rubber connecting pipe for drainage system according to claim 1, characterized in that: The preparation of the copper-mercaptobenzimidazole / boron nitride is as follows: Copper sulfate pentahydrate and 2-mercaptobenzimidazole are dissolved in deionized water, and then boron nitride nanosheets are added and mixed evenly to obtain solution A. NaBH4 and NaOH are dissolved in deionized water to form solution B. Solution A and solution B are mixed and stirred at room temperature for 1 hour. After complete precipitation, they are filtered and washed, and then dried to obtain copper-mercaptobenzimidazole / boron nitride.

4. The self-cleaning rubber connecting pipe for drainage system according to claim 3, characterized in that: The molar ratio of copper sulfate pentahydrate to 2-mercaptobenzimidazole in the solution A is 1:

1.

5. The self-cleaning rubber connecting pipe for drainage system according to claim 3, characterized in that: The concentration of copper sulfate pentahydrate in the solution A is 0.005 mol / L.

6. The self-cleaning rubber connecting pipe for drainage system according to claim 3, characterized in that: The mass ratio of boron nitride to copper sulfate pentahydrate in the solution A is 1:0.5-2.

7. The self-cleaning rubber connecting pipe for drainage system according to claim 3, characterized in that: The concentration of NaBH4 in the B solution is 0.02 mol / L.

8. The self-cleaning rubber connecting pipe for drainage system according to claim 3, characterized in that: The NaOH concentration in the B solution is 0.08 mol / L.

9. The self-cleaning rubber connecting pipe for drainage system according to claim 3, characterized in that: The volume ratio of solution A to solution B is 9:

1.

10. The self-cleaning rubber connecting pipe for drainage system according to claim 1, characterized in that: The preparation of the rubber connecting pipe is as follows: Put EPDM rubber into an internal mixer, add polytetrafluoroethylene at 150°C and mix for 10 minutes, then add copper-mercaptobenzimidazole / boron nitride, mix for 5 minutes, add carbon black, calcium carbonate, paraffin oil and zinc oxide in sequence, continue mixing for 30 minutes, extrude and place for 10 hours to obtain a mixture, add an accelerator to the mixture, perform vulcanization and molding treatment, and obtain a rubber connecting pipe.

Citation Information

Cited By

  • High-performance engine lubricating oil and preparation method thereof

    CN120505136A